Maudu Lompoa Culture in Shaping The Character of Loving The Environment - Hendra, Hendra; Mahat, Hanifah; Rusdi, Rusdi (UIN Maulana Malik Ibrahim Malang, 2023)
Environmental damage is a recurring issue in South Sulawesi. The community remains insufficiently aware of the importance of environmental conservation. One of the contributing factors is the lack of a character that values and loves the environment within the community. It is necessary to integrate local culture into environmental issues. Society should recognize that integrating knowledge and personal norms inherited from their ancestors can shape an environmentally friendly character. This research examines how Maudu Lompoa culture shapes an environmentally aware character among the followers. The research findings reveal that the formation of an environmentally aware character in Maudu Lompoa is rooted in the love and devotion to the Prophet Muhammad (peace be upon him) as a holy figure. Maudu Lompoa is conducted with great reverence at each stage, emphasizing cleanliness and the sanctity of the celebration process. The formation of an environmentally aware character stems from behavioral patterns and ancestral messages, which are embodied in preparing celebration materials, food, and event venues. This study could shape the community's understanding of environmental preservation and inspire a lifelong love of the environment ingrained in their values. Kerusakan lingkungan di Sulawesi Selatan masih sering terjadi. Masyarakat masih kurang menyadari pentingnya menjaga lingkungan. Kurangnya karakter cinta lingkungan dalam diri masyarakat menjadi salah salah satu penyebabnya. Diperlukan integrasi budaya lokal dalam permasalahan lingkungan. Masyarakat harus menyadari bahwa integrasi pengetahuan dan norma-norma pribadi dari leluhur sangat penting untuk membentuk karakter cinta lingkungan. Penelitian ini mengkaji tentang budaya lokal Maudu Lompoa dengan fokus pada pelaksanaannya yang membentuk karakter cinta lingkungan para pengikutnya. Temuan penelitian mengungkapkan bahwa pembentukan karakter cinta lingkungan pada pelaksanaan Maudu Lompoa dibentuk oleh landasan kecintaan kepada Nabi Muhammad SAW sebagai manusia suci. Pelaksanaan Maudu Lompoa dilaksanakan dengan penuh khidmat dari setiap tahapannya dengan memperhatikan kebersihan dan kesucian prosesi perayaan. Pembentukan karakter cinta lingkungan terbentuk dari bentuk perilaku dan pesan-pesan leluhur, yang tetuang dalam perilaku menyiapkan bahan perayaan, makanan, dan tempat pelaksanaan. Penelitian ini dapat memberikan implikasi pada pengetahuan masyarakat dalam menjaga lingkungan sekitarnya, membentuk karakter cinta lingkungan yang akan bertahan lama karena berasal dari kepercayaan yang dianutnya